Understanding the Perceptions of Producers Regarding the Ogallala Aquifer Use: A Survey Report - Jonathan Aguilar; Amariah Fischer; Matthew R Sanderson (Kansas Agricultural Experiment Station Research Reports, 2022)
This survey asked producers in the Ogallala aquifer how they view their role in groundwater use, what they see as the consequences of groundwater depletion, and why they believe groundwater should be conserved. Producers were also asked about their worldviews and values. Together, these questions help provide an understanding of the cultural state of the Ogallala aquifer, especially as it pertains to groundwater use.
Keywords: Ogallala Aquifer; groundwater use; producer perception; groundwater conservation